Money supply and the implementation of interest rate targets - Andreas Schabert (European Central Bank (ECB), 2005)
In this paper, we analyze the relation between interest rate targets and money supply in a (bubble-free) rational expectations equilibrium of a standard cash-in-advance model. We examine contingent monetary injections aimed to implement interest rate sequences that satisfy interest rate target rules. An interest rate target with a positive inflation feedback in general corresponds to money growth rates rising with inflation. When prices are not completely flexible, this implies that a non-destabilizing money supply cannot implement a forward-looking and active interest rate rule. This principle also applies for an alternative model version with an interest elastic money demand. The implementation of a Taylor-rule then requires a money supply that leads to explosive or oscillatory equilibrium sequences. In contrast, an inertial interest rate target can be implemented by a non-destabilizing money supply, even if the inflation feedback exceeds one, which is often found in interest rate rule regressions.
Keywords: E52; E41; E32; 330; contingent money supply; interest rate inertia; interest rate rules; macroeconomic stability; policy equivalence; Geldmenge; Zinspolitik; Zielzone; Regelbindung versus Diskretion; Rationale Erwartung